Solitary intraosseous neurofibroma: Report of a unique case - Sagar Satish Jangam; Snehal Nilesh Ingole; Mohan Devidas Deshpande; Pallavi Adinath Ranadive (Wolters Kluwer Medknow Publications, 2014)
Neural tumors located centrally in jaw bones are relatively rare compared with soft tissue neurofibromas. Less than 50 cases have been reported in the literature with a predilection for mandible. This article aims to elucidate a unique case of intraosseous neurofibroma of mandible in a 62-year-old edentulous female patient associated with facial asymmetry due to the swelling extending from the right body of mandible to left body of mandible. The uniqueness of this case is related to the age and extensiveness of this lesion. A review of clinical, radiographic, histological, and immunohistochemical features, and the surgical management pertaining to this case are discussed along with a review of the literature.